Deep Deltoid Ligament Reconstruction Utilizing Suture Augmentation via an Arthroscopically- Assisted Approach: A Novel Technique and Case Series - Frederic J. Washburn DO; Conner S. Roggy DO; Britni Tran BS; Casey W. Pyle DO; Thomas G. Harris MD (Foot & Ankle Orthopaedics, 2023)
Category: Trauma; Arthroscopy Introduction/Purpose: Deltoid ligament rupture is a common occurrence in the setting of acute ankle fractures. The indications for surgical restoration of the deltoid ligament complex vary considerably throughout the literature. If medial ankle instability exists after ankle fracture fixation, repair or reconstruction of the deltoid ligament complex may be performed, which is traditionally done via an open approach. While the superficial deltoid is easily accessed with an open approach, the deep deltoid ligament is extremely difficult to visualize. We present a novel technique for reconstruction of the deep deltoid ligament complex utilizing suture augmentation via an arthroscopically-assisted approach and present our outcomes. With this method, the deep deltoid ligament disruption is easily visualized and reconstructed in a minimally invasive manner through an accessory anteromedial arthroscopy portal. Methods: This is a technique guide and retrospective case series. Data was obtained via chart review including pre-operative, intraoperative, and post-operative follow ups. Variables such as age, weight, body mass index (BMI), sex, side, history of previous ankle surgery, preoperative ambulatory status, length of hospital stay, as well as disposition were documented. Radiographs were reviewed for evidence of restoration of the medial clear space as well as hardware position and bony union. In addition, a technique guide was developed using expert surgeon experience and opinion while using this novel technique. Results: 7 patients who underwent this novel technique were reviewed with an average follow up time of six months (3-8 months). All patients suffered bimalleolar or trimalleolar equivalent fractures. Patients were indicated for deep deltoid ligament reconstruction if medial ankle instability existed intraoperatively with valgus stress testing under fluoroscopy. Medial clear space decreased from a mean 11mm preoperatively to 3.3mm postoperatively. 6 patients returned to ambulation without brace by three months postoperatively. One patient demonstrated increased medial clear space measured at 6.6mm postoperatively and residual pain on follow up, but was treated conservatively and able to progress to weight bearing as tolerated by 6 months. One patient developed a keloid scar that required a steroid injection. No postoperative infections occurred. Conclusion: Deep deltoid ligament reconstruction utilizing suture augmentation via an arthroscopically-assisted approach should be considered in patients who have residual medial ankle instability after ankle fracture fixation. This novel technique allows visualization of the deep deltoid ligament complex and reconstruction in a minimally invasive manner via an accessory anteromedial arthroscopy portal. Our short term outcomes demonstrate success in restoring ankle function and radiographic parameters of the medial clear space. Further studies are needed to evaluate long term postoperative functional outcomes, stability, and development of post-traumatic arthritis.